Learning experience design of verbal prompts in virtual reality-based training for autistic children - Jewoong Moon (Association for Learning Technology, 2024)
This study aimed to explore the design and development of verbal prompts in virtual reality (VR)-based social skills training for autistic children. Autism indicates a category with neurodiversity that influences individuals' capability to engage in social and cognitive tasks. This complex neurodevelopmental condition manifests in a wide array of patterns, featuring unique experiences of each individual. This study explored both advantages and challenges encountered when autistic children interact with verbal prompts in multi-user, desktop VR-based social skills training. Our explanatory case study involved VR-based learning experiences of four autistic children. We used a qualitative thematic analysis to analyse the study participants' interaction patterns with verbal prompts in the VR-based training. Our research can contribute to both theoretical knowledge and practical design guidelines for the creation of verbal prompts in desktop VR-based training programmes tailored for autistic children.